Utility and A-Based Algorithm for Network Slice Placement and Chaining - Aklamanu, Fred; Randriamasy, Sabine; Renault, Eric (IEEE Global Communications Conference (Online), 2019)
Next Generation Mobile Network, 5G, will leverage heavily on Network Function Virtualisation for flexible and cost efficient deployments. 5G technology is to provide numerous innovative business opportunities through a key concept known as Network Slicing. This approach will require efficient placement and chaining of virtual network functions (VNFs) composing a network slice. The goal is to maximize network resources availability with minimal cost as network infrastructure is shared among different network slices. This paper proposes a time and resource-efficient VNF placement and chaining method, UA*, a Utility-based placement algorithm that extends the A* algorithm node classification set. UA* considers slice performance requirements and policies. Our simulations evaluate UA* and compares its performance with state of the art approaches.